Transcription factor mesenchyme homeobox protein 2 (MEOX2) modulates nociceptor function. (16th February 2022) - Kokotović, Tomislav; Lenartowicz, Ewelina M.; Langeslag, Michiel; Ciotu, Cosmin I.; Fell, Christopher W.; Scaramuzza, Angelica; Fischer, Michael J. M.; Kress, Michaela; Penninger, Josef M.; Nagy, Vanja
Abstract : Mesenchyme homeobox protein 2 (MEOX2) is a transcription factor involved in mesoderm differentiation, including development of bones, muscles, vasculature and dermatomes. We have previously identified dysregulation of MEOX2 in fibroblasts from Congenital Insensitivity to Pain patients, and confirmed that btn, the Drosophila homologue of MEOX2, plays a role in nocifensive responses to noxious heat stimuli. To determine the importance of MEOX2 in the mammalian peripheral nervous system, we used a Meox2 heterozygous ( Meox2 +/− ) mouse model to characterise its function in the sensory nervous system, and more specifically, in nociception. MEOX2 is expressed in the mouse dorsal root ganglia (DRG) and spinal cord, and localises in the nuclei of a subset of sensory neurons. Functional studies of the mouse model, including behavioural, cellular and electrophysiological analyses, showed altered nociception encompassing impaired action potential initiation upon depolarisation. Mechanistically, we noted decreased expression of Scn9a and Scn11a genes encoding Nav 1.7 and Nav 1.9 voltage‐gated sodium channels respectively, that are crucial in subthreshold amplification and action potential initiation in nociceptors. Further transcriptomic analyses of Meox2 +/− DRG revealed downregulation of a specific subset of genes including those previously associated with pain perception, such as PENK and NPY . Based on these observations, we propose a novel role of MEOX2 in primary afferent nociceptor neurons for the maintenance of a transcriptional programme required for proper perception of acute and inflammatory noxious stimuli. Abstract : Mesenchyme homeobox protein 2 (MEOX2) is a transcription factor important for the development of bones and muscles. We report that MEOX2 is expressed in the nervous system, particularly localised to nociceptive dorsal root ganglia neurons, responsible for pain detection. Our multidisciplinary study of haploinsufficient MEOX2 mouse model revealed that MEOX2 is responsible for fine‐tuning nociceptor action potential generation and behavioural responses to noxious stimuli by regulation of pain gene expression, including particular sodium channel subunits.